Production and Marketing of Rapeseed-Mustard Crop in Bastar Plateau of Chhattisgarh, India: An Economic Analysis - O. P. Sonvanee; H. Pathak (Business, Management and Economics: Research Progress Vol. 7, 2024)
The present study examines the economic analysis of the production and marketing of rapeseed-mustard in the Bastar Plateau of Chhattisgarh State, India. Rapeseed-mustard belongs to the family Cruciferae and the genus Brassica. Rapeseed (Brassica compestris) commonly called Sarson or Toria is an herbaceous annual plant shorter than mustard (rai) between 45-150 cm. Mustard (Brassica juncea) common name is called rai. The study was conducted in the Tokapal and Lohandiguda blocks in the Bastar district of Chhattisgarh State, India. Fifty-two farmers were selected randomly from ten villages from these blocks to collect the required information on the cost of cultivation, marketing and other aspects for the present study. The primary data was collected from the rapeseed-mustard producers through personal interview method with the help of a well-prepared schedule and questionnaire for the production and post-harvest year for rabi rapeseed-mustard 2013-14. To examine the marketing pattern of major oilseeds at different categories of farms, a simple analysis was done. The average cost of cultivation and the input-output ratio of rapeseed-mustard was worked out as Rs. 11030.14/ha. and 1: 1.23. The average Cost A1, Cost B1, Cost B2, Cost C1, Cost C2 and Cost C3 were observed as Rs.11026.84, Rs.11529.45, Rs.18121.71, Rs.19231.26, Rs.25823.47 and Rs.18405.81 per hectare. The three types of marketing channels identified in the study area were Channel-I: Producer – Village trader, Channel-II: Producer – Retailer – Wholesaler and Channel-III: Producer – Wholesaler. The marketable surplus of rapeseed-mustard is observed as 2.85 quintal, 3.60 quintal, 4.00 quintal and 6.74 quintal per farm which is 99.30 per cent, 99.17 per cent, 93.00 per cent and 99.26 per cent to their total production at marginal, small, medium and large farms respectively. The average marketable surplus of rapeseed-mustard is found to be 4.44 quintals constituting 99.32 per cent of the total quantity produced. The quantity of rapeseed-mustard sold per farm was very low which was mainly due to low productivity. Lack of irrigation facilities (89.00 per cent) followed by lack of recommended packages and practices, particularly, doses of fertilizer, insecticides and pesticides were perceived by 84.00 per cent of rapeseed-mustard farmers were major constraints in rapeseed-mustard cultivation. Most of the rapeseed-mustard growers were of the opinion that the crop of rapeseed-mustard is less profitable due to these marketing problems as compared to maize and paddy production in the same type of land situation, in the study area. More than 81.00 per cent of rapeseed-mustard producers perceived that transportation of small quantities of produce was not an economical option if they sold their small produce in the market. The study suggested that urgent attention must be paid to enhancing the productivity and marketing of rapeseed mustard by providing improved and high-yielding varieties, technology, irrigation, marketing, price support, policy and effective extension. The study concluded that direct marketing without agents/ middlemen will help in better marketing of oilseeds. Moreover, the government should take necessary steps for the pricing and implementation of minimum support prices in rapeseed mustard and major oilseeds.